Managing compatibility of economic growth and environmental preservation through environmental impact assessment in Malaysia - Eissa, Garoot Suleiman (2013)
This study is aimed at the assessment of the influence of Environmental Impact assessment (EIA), as a tool of environmental management in Malaysia, on environmental preservation and sustainable development. It is important to realize that achievement of rapid rates of economic growth and environmental preservation are inherently incompatible goals. Environmental degradation is caused by economic growth and development, hence managing both public policy priorities at the same time involves the making of hard choices. In developing countries EIA is seen as a break on development. However, EIA is a preemptive measure carried out during the planning of development projects aimed at enhancing simultaneous achievement of both goals. Its purpose is to block implementation of potentially polluting economic activities. In Malaysia all development projects are subjected to it to some degree. But, there are claims and counter claims in the literature that one goal is sacrificed for the sake of the other. About 19 development activities are targeted for detailed evaluation by the headquarters of the Department of the environment (DOE); while other activities, comprising nearly 80% of development activities, are subject to preliminary assessment by offices of the DOE at the local level. The two types of decisions – based on detailed and preliminary assessment- will be held as independent variables. Whereas, water and air pollution indicators as well as economic growth rates are designated as dependent variables and hypotheses about relationships will be tested. In the case of water pollution, due to availability of time series data, a correlated time series methodology will be adopted. In the case of air pollution acceptable standards of pollution, set by the DOE, will be compared to actual levels at some selected sights of highly industrialized and urbanized areas. Most of the study, it should be pointed out, takes the form of a description of EIA administrative procedures. Policy implications will be discussed